Track and field events at XXXI Olympic Games in Rio de Janeiro - Mirzoev, O. M. (Theory and Practice of Physical Culture, 2017)
Abstract: The article offers a competitive performance analysis of the national teams that won gold medals at the Olympic Games in Rio; considers, among other things, unofficial team standings determined by the gold, silver and bronze medals won in the events; gives detailed performance ratings for the top three teams at the 2016 Olympics in Rio de Janeiro; and makes a comparative team success analysis versus that of the top national track and field competitors at the 2012 Olympic Games in London [3]. Subject to a special analysis were the accomplishments of those teams (including the European ones) who have improved their team standings versus their results in the last Olympics. Study results and discussion. The Rio Olympics demonstrated clear enough that American track and field athletes today are largely beyond competition as the leaders in the team standings, and the domination is underlined by the team scores of their nearest competitors (Kenya and Jamaica) that are by far down on the scoreboard